Job Satisfaction Mediates Organizational Culture and Work Discipline On Employee Performance In The Frontliner Section at PT Bank Central Asia Tbk Kcu Cikarang - Rina Elviana; Fitri Rezeki; Susan Kustiwan (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to examine the influence of organizational culture and work discipline on employee performance through job satisfaction. The approach used in this research is a quantitative. The sample size in this study consists of 42 respondents, all of whom are employees of PT Bank Central Asia Tbk, KCU Cikarang Branch. The research data were obtained from questionnaire responses and analyzed using SEM PLS analysis techniques. The findings of this study conclude that organizational culture does not influence employee performance. However, when mediated by job satisfaction, organizational culture can affect performance. This implies that the existing organizational culture at BCA Bank does not always lead to high employee performance; to ensure that organizational culture improves employee performance, it must enhance employee satisfaction. Work discipline can directly and indirectly influence performance through job satisfaction; employees with high work discipline tend to have high performance, especially if their discipline also enhances their job satisfaction.